2022
DOI: 10.15581/003.35.2.71-87
|View full text |Cite
|
Sign up to set email alerts
|

Brand strategy and content management on Instagram: scheduling and message length as factors to improve engagement

Abstract: Companies use social media in their communication strategy to connect with their audiences via online brand communities and social media fan pages. In this context, the scientific community defines the term ‘engagement’ as the primary metric used to identify the degree to which brand and consumers are organically connected. This phenomenon gets measured by audience interactions with the brand content, which is the main factor stimulating participation and value perception in their relationship with the brand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
2
0
3
Order By: Relevance
“…Otros trabajos anteriores como los de Kanuri et al (2018), Matosas-López y Cuevas-Molano (2021) y el más reciente de Cuevas-Molano et al, (2022), que han implementado este mismo análisis a empresas de otros sectores, desvelan datos similares indicando que las horas de entrada y salida de la jornada laboral hay un mayor grado de Engagement entre los seguidores. En este caso, sí que la mayoría de las marcas analizadas están aprovechando correctamente y de forma eficiente el factor horario en su estrategia para incrementar el grado de Engagement de los consumidores.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Otros trabajos anteriores como los de Kanuri et al (2018), Matosas-López y Cuevas-Molano (2021) y el más reciente de Cuevas-Molano et al, (2022), que han implementado este mismo análisis a empresas de otros sectores, desvelan datos similares indicando que las horas de entrada y salida de la jornada laboral hay un mayor grado de Engagement entre los seguidores. En este caso, sí que la mayoría de las marcas analizadas están aprovechando correctamente y de forma eficiente el factor horario en su estrategia para incrementar el grado de Engagement de los consumidores.…”
Section: Discussionunclassified
“…En la misma línea, aparece un motivo subyacente al interés de los consumidores en redes sociales y es que aquellas marcas sin presencia en redes sociales provocan una falta de confianza y credibilidad entre los usuarios (IAB Spain, 2023). Esta conexión está atrayendo cada vez más la atención de los responsables de comunicación, que identifican el potencial de estas herramientas y canales para establecer relaciones fieles, duraderas y estables con sus públicos, mejorando, de este modo, lo que se conoce como la estrategia de marca (Cuevas-Molano, 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…This goes along with the findings of Annamalai et al (2021) who found that Facebook content strategies need to adapt depending if it is peak season or offseason. Additionally, Cuevas-Molano et al (2022) point out that brands need to consider their timing schedules for posts to increase engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that both content quality (visuals and text) and media quality (intuitiveness and interactivity) positively impact flow (Cuevas et al, 2021). Combining the Use and Gratification (U & G) Framework (Cuevas-Molano et al, 2022;Katz et al, 1973) and the Technology Acceptance Model (TAM) (Lin et al, 2017;Venkatesh et al, 2007) help explain these impacts by highlighting underlying consumer motivations for consuming certain type of contents through adopting certain media (Florenthal, 2019). U&G theory is a widely used framework to identify and understand consumer motivations for using marketing communications media ( (Halaszovich andNel, 2017) Florenthal, 2019).…”
Section: The Process Of Flow: Theoretical Underpinningsmentioning
confidence: 99%